The assessment of two endodontics methods in terms of the quality of dentists' work and the patients' comfort - Słowik, Joanna (2004)
Many shaping techniques and instruments have been described and constructed in an attempt to minimize apical transportation, zipping and other problems found in root canals. Most root canals are still prepared using conventional finger instruments to ensure the hardness and sharpness required to prepare the dentine walls of the root canals. The recent introduction of nickel titanium alloy to endodontics has solved many of the problems that have been associated with the negative features of stainless steel instruments. Endodontic instruments made from this super-elastic alloy are significantly more flexible and are highly resistant to fracture and corrosion. The evolution of rotary instrumentation, using specially designed Ni-Ti files in gear reduction and high-torque hand pieces, has recently revolutionized endodontics because of their speed and efficacy in canal shaping and maintaining canal curvature. Improvements in rotary techniques resulted in the marketing of Lightspeed instruments from 1993. Basically, these engine-driven nickel titanium instruments have cutting tips which vary in length from 0.25mm for size 20 instruments to 1.75 mm for size 100. The cutting tips have three geometric forms which optimize efficient cutting of dentin. The remainder of the instrument shaft is thin and highly flexible which, with the pilot nose cutting tip, helps in maintaining optimal cen
Keywords: lightspeed instruments; endodontics; comfort of work